Audit Manajemen Risiko Sistem Informasi pada Website Digo.id dengan Framework COBIT 5 dan ISO 31000 - Putra Pamungkas Sukmana; Titan Parama Yoga; Chairul Habibi (Ma'soem University, 2023)
This research was conducted to know, analyze, and audit on information system risk management on Digo.id website. The framework used in this audit research is COBIT 5 and ISO 31000, using qualitative descriptive research methods, these methods are used to obtain results that can be a clear picture of how Risk Management is implemented by the company. The results showed that the Existing Capability is at level 1, while the Capability Target is at level 3 so the final result of this audit is that the company still has 2 Capability GAPs to achieve the Capability Target.